Comparative genomic hybridization on microarray (a‐CGH) in olfactory neuroblastoma: Analysis of ten cases and review of the literature. Issue 12 (10th September 2015) - Valli, Roberto; De Bernardi, Francesca; Frattini, Annalisa; Volpi, Luca; Bignami, Maurizio; Facchetti, Fabio; Pasquali, Francesco; Castelnuovo, Paolo; Maserati, Emanuela
<x xml:space="preserve">Abstract</x> Olfactory neuroblastoma is a rare tumor arising from the basal layer of the olfactory epithelium in the superior recesses of the nasal cavity. The rarity of this tumor, and the difficulties in culturing tumor cells has limited the generation of conventional cytogenetic data, whereas consistent results have been obtained by recent molecular methods. We report the results of an array‐based comparative genomic hybridization analysis (a‐CGH) obtained on 11 samples from 10 subjects: 8 primary and 3 relapsed tumors. In one patient, both the primary and relapsed tumors were available. Our results on chromosome imbalances highlight the highly heterogeneous presentation: six of eleven samples showed multiple numerical changes and very few structural ones, while four samples showed an opposite pattern; one sample out of eleven showed no imbalances. We did not reach firm evidence of any recurrent specific imbalances either at level of entire chromosomes or chromosome segments. A review of the literature indicates a number of recurrent gains, and losses, mostly not confirmed by our results. Gain of chromosome 19 was the only correspondence with literature data concerning an entire chromosome, and most segmental gains and losses found in our cohort of patients were different from those indicated in the literature: the only similarities concerned the gain of 20q13 and the loss of segments of chromosomes 15 and 22. © 2015 Wiley Periodicals, Inc.